Magnetic body structure, method for manufacturing the same, and electronic device

CN119920563BActive Publication Date: 2026-10-09DONGGUAN SUNLORD ELECTRONICS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411927864.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2026-10-09
Estimated Expiration
2044-12-25

AI Technical Summary

Technical Problem

[0007]本申请公开了磁性体结构及其制备方法和电子设备,通过在磁性体主体的孔洞内填充树脂,封堵住磁性体主体的孔洞,并在磁性体表面上设置膜层,解决了磁性体结构在传统制造过程中由于孔洞导致的机械强度不足、绝缘性能差以及易发生生锈和爆米花现象等问题

Benefits of technology

[0025] The magnetic structure described in this application, by filling the pores of the magnetic body with resin, can reduce magnetic flux leakage caused by pores generated during sintering, thereby enhancing the overall strength of the magnetic structure. The film layer formed on the surface of the magnetic body can improve the insulation performance of the magnetic structure, prevent current leakage, and simultaneously isolate moisture and oxygen in the air, preventing the magnetic body from rusting and extending the product's service life. Therefore, this application improves the magnetic strength and insulation performance of the magnetic structure, as well as prevents rusting and popcorn effect, thus improving product reliability and process yield.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119920563B_ABST
    Figure CN119920563B_ABST
Patent Text Reader

Abstract

The present application relates to the technical field of magnetic structure, and particularly relates to a magnetic structure, a preparation method thereof and an electronic device. The present application discloses a magnetic structure, comprising: a magnetic body main body formed by sintering soft magnetic alloy powder; a resin filled in a hole of the magnetic body main body; and a film layer arranged on a surface of the magnetic body main body; the magnetic structure satisfies: magnet strength > 120 N and / or resistance > 100 kΩ. The magnetic structure disclosed by the present application fills the resin in the hole of the magnetic body main body, blocks the hole of the magnetic body main body, and arranges the film layer on the surface of the magnetic body, so as to solve the problems of insufficient mechanical strength, poor insulation performance, easy rusting and popcorn phenomenon of the magnetic structure caused by the hole in the traditional manufacturing process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the technical field of magnetic structures, specifically to a magnetic structure, its preparation method, and an electronic device. Background Technology

[0002] With the rapid development of the electronic components industry, high-current, miniaturized, and high-efficiency electronic components have become the core trend in current product design. Against this backdrop, the rapid growth of the AI ​​server market has placed higher performance demands on magnetic components such as power inductors, requiring high reliability, high saturation characteristics, and low losses. To meet these needs, the selection and preparation technologies of magnetic materials are constantly being innovated. Due to its excellent electromagnetic properties and machinability, Fe-based soft magnetic alloy powder has gradually replaced traditional ferrite materials, becoming the preferred choice for high-performance magnetic components.

[0003] However, the preparation of Fe-based soft magnetic alloy powder faces the following challenges. First, during high-temperature sintering, the atoms in the alloy powder rearrange to form a crystalline structure. Simultaneously, organic materials such as resins in the powder decompose, creating pores of varying sizes. These pores not only reduce the mechanical properties of the magnet, such as strength and toughness, but also become channels for impurities like moisture and dust to penetrate, leading to insulation failure, rusting, and the "popcorn effect," severely impacting product reliability and lifespan.

[0004] To address the aforementioned issues, current solutions primarily focus on two aspects: first, optimizing sintering process parameters, such as lowering the sintering temperature and extending the holding time, to reduce the formation of voids; and second, employing post-processing techniques, such as surface coating and impregnation, to encapsulate and protect the magnets. However, while optimizing the sintering process can reduce the number of voids to some extent, it often comes at the cost of sacrificing electromagnetic properties and cannot completely eliminate voids. While surface coating and impregnation methods can improve the insulation and rust resistance of the magnets, the adhesion between the coating and the magnet substrate is weak, making it prone to detachment under stress or temperature changes, thus affecting the long-term stability of the product.

[0005] Furthermore, existing technologies still present significant challenges in fabricating pore-free or low-porosity magnetic structures. On one hand, the formation mechanism of pores during high-temperature sintering is complex and difficult to fully control through simple process adjustments. On the other hand, post-processing often requires the formation of a thick coating on the magnet surface, which not only increases the product's volume and weight but may also adversely affect its electromagnetic properties.

[0006] Therefore, developing a magnetic structure, its preparation method, and electronic devices that can effectively improve the strength and insulation of magnets, solve the problems of magnet rusting and popping, and do not affect the adhesion of the outer coating, has become an urgent technical problem to be solved. Summary of the Invention

[0007] This application discloses a magnetic body structure, its preparation method, and an electronic device. By filling the pores of the magnetic body with resin to seal the pores and setting a film layer on the surface of the magnetic body, the problems of insufficient mechanical strength, poor insulation performance, and easy rusting and popcorn effect caused by pores in the traditional manufacturing process of magnetic body structures are solved.

[0008] The objective of this invention is achieved through the following technical solution:

[0009] In a first aspect, this application provides a magnetic body structure, comprising:

[0010] The main body of the magnetic material is formed by sintering soft magnetic alloy powder;

[0011] Resin is used to fill the pores in the main body of the magnetic material.

[0012] A film layer is disposed on the surface of the magnetic body;

[0013] The magnetic body structure satisfies the following conditions: magnet strength > 120N and / or resistance > 100kΩ.

[0014] In some specific embodiments, the resin is any one or more of phenolic resin, epoxy resin, silicone resin, acrylic resin, and imide resin.

[0015] In some specific embodiments, the resin is distributed at a depth of ≥30μm inside the magnetic body.

[0016] In some specific embodiments, the coefficient of thermal expansion of the resin is <1.0 ppm / ℃.

[0017] In some specific embodiments, the thickness of the film layer is ≥1μm and / or the touch-drying time of the film layer is ≤20min.

[0018] In some specific embodiments, the thickness of the film layer is ≥3μm; and / or the touch-drying time of the film layer is ≤10min.

[0019] In some specific embodiments, a coating layer is also provided on the membrane layer.

[0020] In some specific embodiments, the soft magnetic alloy powder is an Fe-based soft magnetic alloy powder.

[0021] Secondly, this application provides a method for preparing the magnetic structure described in the first aspect, comprising the following steps:

[0022] The resin is introduced into the pores of the magnetic body through vacuum pressure impregnation; and the resin is centrifuged to form a film on the surface of the magnetic body.

[0023] Thirdly, this application provides an electronic device, including the magnetic structure described in the first aspect or the magnetic structure prepared by the preparation method described in the second aspect.

[0024] The beneficial effects of this application are:

[0025] The magnetic structure described in this application, by filling the pores of the magnetic body with resin, can reduce magnetic flux leakage caused by pores generated during sintering, thereby enhancing the overall strength of the magnetic structure. The film layer formed on the surface of the magnetic body can improve the insulation performance of the magnetic structure, prevent current leakage, and simultaneously isolate moisture and oxygen in the air, preventing the magnetic body from rusting and extending the product's service life. Therefore, this application improves the magnetic strength and insulation performance of the magnetic structure, as well as prevents rusting and popcorn effect, thus improving product reliability and process yield.

[0026] The preparation method described in this application introduces resin into the pores of the magnetic body through vacuum pressure impregnation, which can reduce the number of pores or the gap between pores, thereby reducing magnetic flux leakage and improving the mechanical strength and magnetic properties of the magnetic body structure. At the same time, the film layer formed by the resin on the surface of the magnetic body can improve the insulation performance of the magnetic body structure and prevent current leakage.

[0027] The electronic device described in this application, by using a magnetic structure with enhanced magnet strength and insulation capabilities, can improve the performance of components such as power inductors in electronic devices, thereby meeting the development needs of high current, miniaturization, and high efficiency. Attached Figure Description

[0028] The present invention will be further described below with reference to the accompanying drawings and embodiments.

[0029] Figure 1 This is a schematic diagram of the magnetic body structure described in this invention.

[0030] Wherein: 1-Magnetic body; 2-Resin; 3-Film layer; 4-Metal particles; 5-Coating layer; 6-Pore. Detailed Implementation

[0031] To facilitate understanding by those skilled in the art, the present invention will be further described below with reference to embodiments. The content mentioned in the embodiments is not intended to limit the present invention.

[0032] As used herein, “and / or” includes all combinations of any and one or more of the associated listed items. The terminology used herein is for the purpose of describing particular embodiments only and is not intended to limit the invention. As used herein, the singular forms “a,” “an,” “an,” and “the” are also intended to include the plural forms unless the context clearly indicates otherwise. Further understanding is needed; when used in this specification, “comprising” designates the stated features, integers, steps, operations, elements, and / or components, but does not exclude the presence or addition of one or more other features, integers, steps, operations, elements, components, and / or combinations thereof.

[0033] Unless otherwise defined, all terms used herein (including technical and scientific terms) have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains. Further understanding is that terms, such as those defined in common dictionaries, are interpreted in accordance with their meaning in the context of the relevant field and are not idealized or overly formal, unless expressly defined herein.

[0034] The exemplary invention described herein may suitably omit any one or more limiting elements, which are not specifically disclosed herein. Therefore, terms such as “comprising,” “including,” “containing,” etc., should be interpreted broadly and non-limitingly. Furthermore, the terminology used herein is for descriptive purposes without limitation, and it is unintentional to use terms that do not include any equivalent characteristics, but only to describe a portion of their characteristics; however, various modifications are possible within the scope of the invention according to the claims. Therefore, while the invention has been specifically disclosed through preferred embodiments and optional features, variations of the invention embodied by the modifications disclosed herein may be noted by those skilled in the art, and such modifications and variations are considered to be within the scope of the invention.

[0035] All raw materials or reagents used in the embodiments and comparative examples of this invention were purchased from mainstream manufacturers on the market. Those without specified manufacturers or concentrations are all analytical grade raw materials or reagents that are routinely available. There are no particular restrictions as long as they achieve the expected effect. The instruments and equipment used in this embodiment were all purchased from major manufacturers on the market. There are no particular limitations as long as they achieve the expected effect. Where specific techniques or conditions are not specified in this embodiment, they shall be performed in accordance with the techniques or conditions described in the literature in this field or according to the product instructions.

[0036] Terminology Explanation:

[0037] The coefficient of thermal expansion refers to the degree of volume change of a material when the temperature rises or falls. For magnetic structures, it is crucial to select a suitable resin material to match the thermal expansion characteristics of the magnetic body, especially in working environments where temperature changes are frequent or significant, as differences in the coefficient of thermal expansion can cause a series of negative effects.

[0038] Metal particles, specifically referring to dispersed metal particles in the structure of a magnetic body, are usually iron or other metal components in Fe-based soft magnetic alloy powder. The presence of metal particles during the sintering process is one of the reasons for the formation of pores.

[0039] To address the problems of insufficient mechanical strength, poor insulation, and susceptibility to rusting and popping caused by voids in traditional manufacturing processes of magnetic structures, this application provides, for example... Figure 1 The magnetic body structure shown includes:

[0040] The magnetic body 1 is formed by sintering soft magnetic alloy powder;

[0041] Resin 2 is filled into the holes 6 of the magnetic body 1;

[0042] A film layer 3 is disposed on the surface of the magnetic body 1;

[0043] The magnetic body structure satisfies the following conditions: magnet strength > 120N and / or resistance > 100kΩ.

[0044] Specifically, the above-mentioned technical solution effectively enhances the overall structural strength of the magnetic body by filling the pores with resin, thus solving the problem of insufficient mechanical strength caused by the pores. The film layer, formed by resin on the surface of the magnetic body, significantly improves the insulation resistance and reduces the risk of short circuits caused by moisture intrusion. Therefore, the magnetic body structure satisfies the following requirements: magnetic strength > 120N and / or resistance > 100kΩ.

[0045] Through the above technical solution, resin filling of pores can prevent external moisture from entering the interior of the magnetic body, avoiding rust and the popcorn effect that may occur during patching, thereby greatly improving the long-term stability and reliability of the product.

[0046] Understandably, the magnetic structure meets the requirements of a magnet strength > 120N and / or a resistance > 100kΩ, which enables the magnetic structure to achieve high standards in terms of mechanical strength and electrical insulation, meeting the needs of high-end applications.

[0047] In one or more embodiments, the soft magnetic alloy powder is an Fe-based soft magnetic alloy powder, which can provide the magnetic properties required for the magnetic body structure, including high saturation magnetic induction and low loss characteristics.

[0048] Specifically, Fe-based soft magnetic alloy powder is mainly composed of iron (Fe), and other elements such as silicon (Si), aluminum (Al), and chromium (Cr) can be added in certain proportions as needed to adjust its physical and electromagnetic properties.

[0049] It is understandable that during the sintering process of Fe-based soft magnetic alloy powder, due to gaps and expansion and contraction between metal particles 4, pores 6 are present in the magnetic body 1 after sintering. These pores exist both inside and on the surface of the magnetic body.

[0050] In one or more embodiments, the resin is any one or more of phenolic resin, epoxy resin, silicone resin, acrylic resin, and imide resin. The specific type of resin can be selected according to actual needs.

[0051] In practical applications, magnetic structures may experience significant temperature fluctuations. If the coefficient of thermal expansion of the resin material is too high, it may lead to uneven thermal stress between the resin and the magnetic body, resulting in deformation or damage to the magnetic structure. Therefore, in this application, the coefficient of thermal expansion of the resin is <1.0 ppm / ℃, meaning a low coefficient of thermal expansion is required. A low coefficient of thermal expansion results in a higher degree of compatibility between the resin and the magnetic body when used in different temperature environments, reducing the risk of damage due to thermal cycling and thus improving the long-term reliability and service life of the product. Therefore, by selecting a resin with a coefficient of thermal expansion <1.0 ppm / ℃ in this application, the dimensional stability of the magnetic structure can be maintained during temperature changes, avoiding stress and deformation caused by thermal expansion and contraction, and significantly reducing the risk of deformation or damage to the magnetic structure.

[0052] Specifically, the coefficient of thermal expansion of the resin can be selected from any value among 0.75ppm / ℃, 0.80ppm / ℃, 0.85ppm / ℃, 0.88ppm / ℃, 0.90ppm / ℃, and 0.95ppm / ℃, as long as it is <1.0ppm / ℃.

[0053] In one or more embodiments, the thickness of the film layer is ≥1μm and the touch drying time is ≤20min.

[0054] Specifically, the film thickness is ≥1μm, for example, it can be any value among 1μm, 1.5μm, 2μm, and 2.5μm; a film thickness of ≥1μm can ensure that the resin material can fully cover the surface of the magnetic material, forming a continuous and dense protective layer, effectively sealing the pores and improving the insulation performance.

[0055] With a touch-drying time of ≤20 min, the resin can cure in a shorter time, reducing processing cycles, increasing production line turnover, and lowering production costs. The specific touch-drying time can be any value among 20 min, 19 min, 18 min, and 17 min.

[0056] Preferably, the thickness of the film layer is ≥3μm, for example, it can be any value among 3μm, 3.5μm, 4μm, and 4.5μm; the touch drying time of the film layer is ≤10min, for example, it can be any value among 10min, 9min, 8min, and 7min.

[0057] In one or more embodiments, a coating layer 5 is further provided on the membrane layer 3.

[0058] Specifically, while the resin-formed film currently provides preliminary rust protection, corrosion risks may still exist in certain extreme environments (such as high humidity and salt spray). The coating provides a double protective barrier for the magnetic material, significantly reducing the likelihood of rust and corrosion. The coating can be formed by curing epoxy resin or polyurethane.

[0059] More specifically, epoxy resin, due to its excellent adhesion and electrical insulation properties, is often used for coating electronic components. It can undergo a cross-linking reaction with the active groups in the underlying resin during high-temperature curing, forming a strong interfacial bond.

[0060] Polyurethane: It has good flexibility and chemical resistance, making it suitable for applications requiring impact or abrasion resistance.

[0061] In one or more embodiments, the resin is distributed at a depth of ≥30μm inside the magnetic body.

[0062] Specifically, during the sintering process, Fe-based soft magnetic alloy powder forms pores of varying sizes, which weaken the mechanical strength of the magnetic material. By filling these pores with resin to a depth of ≥30μm (e.g., any value among 30μm, 33μm, 35μm, 40μm, and 45μm), these pores can be effectively sealed, preventing the intrusion of moisture and other harmful substances, thereby improving the overall structural strength and stability of the magnetic material. After filling to a certain depth, the compressive and tensile mechanical properties of the magnetic material structure are significantly improved, solving the problem of insufficient mechanical strength caused by pores. Furthermore, the resin filling is not limited to the surface but extends deep into the magnetic material, forming a more complete insulating barrier, reducing the risk of short circuits and improving the overall insulation effect.

[0063] Understandably, the internal distribution depth refers to the depth reached by the resin filling the pores of the magnetic body in the magnetic body structure. For example, this depth is the vertical distance between the resin filling the pores of the magnetic body and the surface of the magnetic body.

[0064] Furthermore, this application provides a method for preparing the aforementioned magnetic structure, comprising the following steps:

[0065] The resin is introduced into the pores of the magnetic body through vacuum pressure impregnation; and the resin is centrifuged to form a film on the surface of the magnetic body.

[0066] Specifically, during vacuum impregnation, the vacuum level is set to > -0.085 MPa to ensure sufficient removal of air and create conditions for resin entry; the vacuum time is set to 30 ± 5 seconds to ensure sufficient vacuum treatment time to expel air from the pores; and the impregnation time is set to > 10 minutes to give the resin sufficient time to penetrate into the pores inside the magnetic body.

[0067] After vacuum impregnation is completed, positive pressure is applied, >0.3 MPa, to push the resin to overcome the influence of surface tension and enter deeper pores;

[0068] After the positive pressure is applied, the resin on the surface of the magnetic body is separated. The separation speed is set to 900±100 r / min and the separation time is 300±30s. The amount of resin residue on the surface of the magnetic body is controlled so that a continuous film is formed on the surface of the magnetic body without affecting the size of the finished product, and the cost can be reduced at the same time.

[0069] Meanwhile, this application provides an electronic device, including the magnetic structure described above.

[0070] In this application, the magnetic structure exhibits higher strength, better insulation, superior rust resistance, and long-term stability, significantly improving the overall performance and reliability of electronic devices, thereby enhancing the product's market competitiveness. Specific electronic devices may include AI servers, automotive electronics, and consumer electronics products.

[0071] AI servers require high reliability, high saturation characteristics, and low loss. The magnetic structure of this application can meet these stringent requirements, thereby improving the stability and performance of the server.

[0072] Automotive electronics require stability under extreme temperature and humidity conditions, and the improved magnetic structure of this application enhances its weather resistance and long-term reliability.

[0073] Consumer electronics products, such as smartphones and tablets, have high requirements for miniaturization and high efficiency. The magnetic structure of this application helps to achieve a more compact design and higher performance.

[0074] The magnetic structure of the present invention will be further described below with reference to specific embodiments and comparative examples:

[0075] Example 1

[0076] A magnetic structure comprising:

[0077] The main body of the magnetic material is formed by sintering soft magnetic alloy powder;

[0078] Resin is used to fill the pores in the main body of the magnetic material.

[0079] A film layer is disposed on the surface of the magnetic body;

[0080] The resin is distributed to a depth of 30 μm inside the magnetic body; the coefficient of thermal expansion of the resin is 0.95 ppm / ℃; the film thickness is 1 μm; and the touch drying time is 10 min.

[0081] Example 2

[0082] A magnetic structure comprising:

[0083] The main body of the magnetic material is formed by sintering soft magnetic alloy powder;

[0084] Resin is used to fill the pores in the main body of the magnetic material.

[0085] A film layer is disposed on the surface of the magnetic body;

[0086] The resin is distributed to a depth of 35 μm inside the magnetic body; the coefficient of thermal expansion of the resin is 0.90 ppm / ℃; the film thickness is 1.5 μm; and the touch drying time is 9 min.

[0087] Example 3

[0088] A magnetic structure comprising:

[0089] The main body of the magnetic material is formed by sintering soft magnetic alloy powder;

[0090] Resin is used to fill the pores in the main body of the magnetic material.

[0091] A film layer is disposed on the surface of the magnetic body;

[0092] The resin is distributed to a depth of 38 μm inside the magnetic body; the coefficient of thermal expansion of the resin is 0.85 ppm / ℃; the film thickness is 1.8 μm; and the touch drying time is 9 min.

[0093] Example 4

[0094] A magnetic structure comprising:

[0095] The main body of the magnetic material is formed by sintering soft magnetic alloy powder;

[0096] Resin is used to fill the pores in the main body of the magnetic material.

[0097] A film layer is disposed on the surface of the magnetic body;

[0098] The resin is distributed to a depth of 40 μm inside the magnetic body; the coefficient of thermal expansion of the resin is 0.83 ppm / ℃; the film thickness is 2.0 μm; and the touch drying time is 8 min.

[0099] Comparative Example 1

[0100] A magnetic structure with a resin having a coefficient of thermal expansion of 1.5 ppm / ℃; all other conditions are the same as in Example 1.

[0101] Comparative Example 2

[0102] A magnetic body structure, wherein the resin is distributed at a depth of 15 μm inside the magnetic body; the remaining conditions are the same as in Example 1.

[0103] Comparative Example 3

[0104] A magnetic structure with a film thickness of 0.3 μm; all other conditions are the same as in Example 1.

[0105] Examples 1-4 and Comparative Examples 1-3 above all used the same batch and model of magnetic body; the size of the magnetic body was 9.0*8.0*2.3mm; the magnetic body was formed by sintering Fe-based soft magnetic alloy powder; the resin used was phenolic resin; the specific method for preparing the magnetic body structure included the following steps:

[0106] Under conditions of vacuum degree > -0.085 MPa and vacuum time of 30 ± 5 seconds, the gas in the pores of the magnetic body is first removed, and the resin is introduced into the pores inside the magnetic body. After the resin fills the pores, the resin is allowed to enter deeper pores under a pressure of 0.3 MPa. After the positive pressure is applied, the resin on the surface of the magnetic body is separated. The separation speed is set to 900 ± 100 r / min and the separation time is 300 ± 30 s, so that a continuous film layer is formed on the surface of the magnetic body.

[0107] The magnetic structures prepared in Examples 1-4 and Comparative Examples 1-3 were subjected to tests for magnet strength and resistance. The test results are summarized in Table 1. The magnet strength was obtained by testing the core bending strength using an automatic push-pull tester. The resistance value was obtained by testing with a resistance meter.

[0108] Table 1

[0109] Example 1 145.3 155.2 Example 2 178.8 183.3 Example 3 221.9 218.6 Example 4 269.9 252.6 Comparative Example 1 144.7 153.9 Comparative Example 2 98.4 149.3 Comparative Example 3 137.5 116.7 Magnetic body 78.6 51.8

[0110] As can be seen from Table 1:

[0111] From Example 1 to Example 4, the magnet strengths of the magnetic structures were 145.3 N, 178.8 N, 221.9 N, and 269.9 N, respectively. This indicates that the magnet strength gradually increases as the resin distribution depth within the magnetic body increases and the resin's coefficient of thermal expansion decreases. This is because the resin fills the pores inside the magnetic body, enhancing the overall structural strength of the magnetic structure. Furthermore, the low coefficient of thermal expansion of the resin helps reduce the risk of stress and deformation caused by temperature changes, thereby improving the mechanical strength of the magnetic structure.

[0112] Meanwhile, from Example 1 to Example 4, the resistance values ​​of the magnetic structure were 155.2kΩ, 183.3kΩ, 218.6kΩ and 252.6kΩ, respectively. Since the continuous film layer formed after the resin fills the pores effectively isolates the direct contact between metal particles, increases the insulation path length, and reduces the possibility of current leakage, the overall insulation performance of the magnetic structure is improved.

[0113] Comparative Example 1 has a magnetic structure with a magnet strength of 144.7 N and a resistance of 153.9 kΩ. Compared to Example 1, the magnet strength and resistance of Comparative Example 1 are slightly lower. This is because the coefficient of thermal expansion of the resin used in Comparative Example 1 is 1.5 ppm / ℃, significantly higher than the 0.95 ppm / ℃ in Example 1. This higher coefficient of thermal expansion may cause uneven thermal stress between the resin and the magnetic body, leading to structural deformation or damage during temperature changes, thus affecting the overall strength and insulation performance of the magnetic structure.

[0114] The magnetic strength of the magnetic structure in Comparative Example 2 was 98.4 N, and its resistance was 149.3 kΩ. The magnetic strength of Comparative Example 2 was significantly lower than that of Example 1, while its resistance was slightly lower. This is because the resin distribution depth within the magnetic body in Comparative Example 2 was only 15 μm, much smaller than the 30 μm in Example 1. The shallower resin distribution could not effectively seal the internal pores, resulting in a significant decrease in the mechanical strength of the magnetic structure. Furthermore, the presence of pores increased the risk of current leakage, thereby reducing the resistance.

[0115] The magnetic strength of the magnetic structure in Comparative Example 3 was 137.5 N, and its resistance was 116.7 kΩ. The magnetic strength of Comparative Example 3 was slightly lower than that of Example 1, but its resistance was significantly lower. The film thickness in Comparative Example 3 was only 0.3 μm, far lower than the 1 μm in Example 1. This is because an excessively thin film cannot provide sufficient protection to completely cover the magnetic surface and form a continuous, dense insulating barrier, thus failing to effectively improve insulation performance and resulting in a lower resistance. Furthermore, although a thinner film may not directly affect the mechanical strength of the magnetic structure, its magnetic strength is also reduced due to poorer overall structural stability.

[0116] The above embodiments are preferred implementations of the present invention. In addition, the present invention can be implemented in other ways. Any obvious substitutions without departing from the concept of the present invention are within the protection scope of the present invention.

Claims

1. A magnetic body structure, characterized in that, include: The main body of the magnetic material is formed by sintering soft magnetic alloy powder; The resin fills the pores of the magnetic body; the resin is distributed at a depth ≥30μm inside the magnetic body; the coefficient of thermal expansion of the resin is <1.0 ppm / ℃. A film layer is disposed on the surface of the magnetic body; the thickness of the film layer is ≥1μm and the touch-drying time of the film layer is ≤20min; The magnetic material structure satisfies the following conditions: magnet strength > 145.3 N and resistance > 155.2 kΩ; The method for preparing the magnetic structure includes the following steps: The resin is introduced into the pores of the magnetic body through vacuum impregnation; and a separation operation is performed to form a film layer on the surface of the magnetic body with the resin; the vacuum degree of the vacuum impregnation is > -0.085 MPa and the positive pressure is > 0.3 MPa.

2. The magnetic structure according to claim 1, characterized in that, The thickness of the film layer is ≥3μm and the touch-drying time of the film layer is ≤10min.

3. The magnetic structure according to claim 1, characterized in that, A coating layer is also provided on the membrane layer.

4. The magnetic structure according to claim 1, characterized in that, The soft magnetic alloy powder is an Fe-based soft magnetic alloy powder.

5. The method for preparing the magnetic structure according to any one of claims 1-4, characterized in that, Includes the following steps: The resin is introduced into the pores of the magnetic body through vacuum impregnation; and a separation operation is performed to form a film layer on the surface of the magnetic body with the resin; the vacuum degree of the vacuum impregnation is > -0.085 MPa and the positive pressure is > 0.3 MPa.

6. An electronic device, characterized in that, The magnetic structure includes any one of claims 1-4 or the magnetic structure prepared by the preparation method described in claim 5.

Citation Information

Patent Citations

  • Manufacturing method of compression molding inductor with high falling performance

    CN116453837A

  • Pressed powder core, method of producing pressed powder core, electric and electronic component, and electric and electronic device

    WO2019198259A1